1999
DOI: 10.1002/(sici)1522-2594(199904)41:4<751::aid-mrm14>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Single‐loop coil concepts for intravascular magnetic resonance imaging

Abstract: Compared with other coil designs that have been investigated for intravascular use, the single-loop coil can be designed with a very small diameter for insertion into small vessels and with a longitudinal extent over several centimeters for multislice imaging. If it designed to be expandable inside the target vessel, then it combines these features with increased signal-to-noise ratio (SNR) and penetration depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…This eliminated susceptibility artifacts in the region of interest (ROI) because local tuning and matching were accomplished with only NPO capacitors. It also enabled remote fine-tuning of the probe without sacrificing signal-to-noise ratio (16,17).…”
Section: Customized Small Animal Coilmentioning
confidence: 99%
“…This eliminated susceptibility artifacts in the region of interest (ROI) because local tuning and matching were accomplished with only NPO capacitors. It also enabled remote fine-tuning of the probe without sacrificing signal-to-noise ratio (16,17).…”
Section: Customized Small Animal Coilmentioning
confidence: 99%
“…In vessels with atherosclerotic plaques interventional MRI has the potential to visualize the morphology of both the vessel wall and the surrounding tissue (2,9,19,(21)(22)(23)(24)(25), whereas conventional angiography is only able to delineate the vessel lumen. The advantages of this information are clear when one considers that the dangers associated with atherosclerosis are not only caused by luminal narrowing but are also dependent on the structure of the vessel wall.…”
Section: Endovascular Interventionsmentioning
confidence: 99%
“…An advantage of utilizing microcoils is the possibility to use the MR signal not only for instrument tracking but also for endovascular imaging or functional studies (19,(23)(24)(25). If, for example, the signals of two solenoid coils are combined, both tracking of the catheter as well as high-resolution imaging of the vessel wall is possible (9,54).…”
Section: Tracking and Profiling Rf Coilsmentioning
confidence: 99%
“…Early work in MR emphasized the fundamental importance of probe integrity (tuning and matching) in achieving a high signal-to-noise ratio (SNR) (10). Several investigators have examined and identified the key tradeoffs for the remote tuning and matching of probes with respect to image quality (11)(12)(13)(14). Tuning is necessary, but it is time-consuming and difficult.…”
mentioning
confidence: 99%